Conformational composition of propanol in gaseous state and in matrix isolation. Issue 1 (2nd November 2022) - Doroshenko, I.; Onuk, M.; Meyliev, L.; Kuyliev, B.
Abstract: Conformational analysis of the experimentally recorded IR absorption spectra of propanol in gaseous state and in a low-temperature argon matrix at 20 K and at 35 K was carried out for different spectral ranges. It showed that the conformational composition of the samples in gas and in matrix isolation is different. In gaseous propanol Gt conformers predominate, while in matrix isolation the most energetically favorable form is Tg conformer, which prevails in percentage at both considered temperatures of an Ar matrix.